Una pagina di Storia della Chimica per la Didattica: lo sviluppo della teoria molecolare della capillarità - Villani, Vincenzo (Chimica nella Scuola, 2024)
The development of understanding of the molecular nature underlying the phenomenon of capillarity and the relation of this with the surface tension underlying the formation of drops and bubbles can become a useful teaching tool in establishing the cause-effect link between the molecular microscopic world and the observed macroscopic world. The chemist uses capillarity in many forms in daily practice, for example in the thin layer chromatography technique, and surface tension in problems of solubility and emulsion stability. However, the depth of these ideas goes far beyond and represents an important page in the history of chemistry and physics, and the development of these concepts is exciting and of educational value. This is a highly interdisciplinary topic, little addressed in teaching programs, but the historical perspective facilitates its exposition and introduces in an innovative way the role of molecular interactions underlying macroscopic phenomena. Although Leonardo already intuited the presence of “hidden” cohesive forces in the formation of a drop, it is in the hands of Laplace’s genius that the molecular theory of capillarity is completely developed and despite the outdated hypothesis, it reaches today. The rise (or lowering) of the level of a liquid in a capillary tube still aroused wonder in the 18th century and greatly disturbed temperature and pressure measurements using liquids in capillary tubes. Today, the idea that it was the gravitational force of the interaction between atoms and molecules responsible for the phenomenon may seem naive, but in truth it was a huge step forward towards a unified vision of the forces of Nature from the atom to the universe. The debate in the 19th century was fierce and profound, it mobilized the greatest minds of the time Laplace, Maxwell, Gauss... Laplace’s theory constituted the solution and the starting point for subsequent studies. The same interactions were placed by the chemist Berthollet at the basis of the chemical affinities, responsible of the reactivity. Then the fundamental laws were deduced, and it was established that the phenomenon of capillarity is due to the surface tension of liquids and this to the short-range attractive and repulsive molecular interactions at the interface.